BUDAYA, IDENTITAS, DAN MEDIA LOKAL - Kristina Andrayani (Profetik: Jurnal Komunikasi, 2015)
Malang society is known as a cultural and local media lovers. It is showed on Walikan language high intencity usage, as well as their high consumption on Malang Post, one of popular local media there. Therefore Malang Post has a Ebes Ngalam rubric that uses Walikan language. With this kind of rubric, Malang Postshows how a local media supports Walikan language as a cultural identity of Malang society. Walikan language it self, was originally considered as a language of symbols for soldiers in 1949 intendedto fool the opponents. One of the method used in the pronunciation of this language is a upside down way which is why the language is known as. The emergence of Ebes Ngalam rubric in Malang Post indicates that thereare struggles to introduce and preserve the cultural identity of Malang society through the use of Walikan language. Based on the background, the research question of this study is: “How does Malang Post maintain local cultural identity through Ebes Ngalam rubric, and how do the audience respond to the message conveyed throughthis walikan language?” Identity theory is underlying the writing of this thesis. It is said that the process of identity is related to cultural aspects that connected straight to identity building and preserving.Media messages are taken from semiotic perspective because usually semiotic tradition consists of someunity symbols which have spatial and chronological arrangements to create effects, idea’s transmiting, or to createmeanings for audience. This study use qualitative descriptive approach which is using Malang Post as the the targetof the study. Futhermore, interview, documentary study, and literature study is used for the data collecting techniques. The data validity is tested by triangulation which utilizes something outside the data to check or compare it. From this study, we can summarize that Malang Post has its own marketing strategy, by using a tagline “as arek Malang newspaper”. It is the main way to embed Malang post as Malang’s identity. The second result is the finding of the new Walikan language vocabularies in Ebes Ngalam rubric. Media purposefully does it so that audience able to receive the content of the message in this rubric. The third finding is about commodification. It is found that there is commodification factor in message content formed in Walikan language.